Dactiloscopia: Importancia en la identificación de un cadáver en Quito-Ecuador en el año 2022. - Arévalo Orejuela, Nelson Fabian (2023)
Dactyloscopy is an auxiliary science of forensics, which allows the reading of fingerprints to identify an individual. For this reason, it is essential to locate bodies in Ecuador through bibliographic review. The bibliographic analysis related to the research topic casts relevant information on the importance of this technique about other methods used for the same purpose, the methods most used for such identification, and the most common failures that do not allow conclusion identifying a corpse. Obtaining statistical data from the Legal Medicine and Forensic Sciences Service of the Metropolitan District of Quito, it is detailed that were 1778 bodies in the year 2022; it was verified that fingerprinting is the most used with a total of 1726 bodies identified, and with a percentage of 97.08%, the analysis indicated that other techniques used are forensic anthropology with 26 identifications corresponding to 1.46%, using Forensics Genetics one body corresponds to 0.06%. In cases of unidentified bodies (NN), it was 25 this year, verifying that influences the state of decomposition of the body, the late cadaveric phenomenon, calcinated bodies, including the wear of the papillary ribs by the advanced age of the corpse.